The Role of Leadership Management in the Development of Leadership Ability in the Person of a Modern Leader - Elmurodov Ulugbek Yusupovich (International Journal on Integrated Education, 2022)
This article focuses on the importance of leadership style in developing leadership skills in modern leaders. A study was conducted on the directive, negligent and collegial methods of management, as well as the emotional intelligence of the leader who determines the attitudes of the labor community. In the correction practice, the directive and negligent styles of the participants achieved a collegial style and increased emotional intelligence.